Environmental enrichment in combination with Bifidobacterium breve HNXY26M4 intervention amplifies neuroprotective benefits in a mouse model of Alzheimer's disease by modulating glutamine metabolism of the gut microbiome - Guangsu Zhu; Min Guo; Jianxin Zhao; Hao Zhang; Gang Wang; Wei Chen (Food Science and Human Wellness)
The gut microbiota-brain axis has emerged as a novel target for Alzheimer's disease (AD), a neurodegenerative disease characterised by behavioural and cognitive impairment. However, most previous microbiome-based intervention studies have focused on single factors and yielded only modest cognitive improvements. Here, we proposed a multidomain intervention strategy that combined Bifidobacterium breve treatment with environmental enrichment (EE) training. In this study, we found that compared with EE or B. breve treatment alone, B. breve intervention combined with EE amplified its neuroprotective effects on AD mice, as reflected by improved cognition, inhibited neuroinflammation and enhanced synaptic function. Moreover, using microbiome and metabolome profiling, we found that the combination of B. breve and EE treatment restored AD-related gut microbiota dysbiosis and reversed microbial metabolite changes. Finally, by integrating behavioural and neurological data with metabolomic profiles, we revealed that the underlying mechanism may involve the modulation of microbiota-derived glutamine metabolism via gut-brain interactions. Collectively, combined B. breve intervention with EE treatment can alleviate AD-related cognitive impairment and improve brain function by regulating glutamine metabolism of the gut microbiome. Our findings provide a promising multidomain intervention strategy, with a combination of dietary microbiome-based and lifestyle-targeted interventions, to promote brain function and delay the progression of AD.